1996
DOI: 10.1007/bf01220804
|View full text |Cite
|
Sign up to set email alerts
|

Thep53 gene is a potent determinant of chemosensitivity and radiosensitivity in gastric and colorectal cancers

Abstract: We previously reported that introduction of the wild-type p53 gene into human cancer cells with deleted p53 enhanced apoptosis induced by chemotherapy [Fujiwara et al. (1994) Cancer Res 54:2287]. This suggests that p53 status could be a potent determinant of the therapeutic efficacy of DNA-damaging cancer therapy. We analyzed 24 patients with gastric or colorectal cancer for p53 mutations and apoptotic changes in surgical specimens. Out of 11 patients with gastric cancer, 3 were treated with chemotherapeutic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
45
0
1

Year Published

1997
1997
2009
2009

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 105 publications
(47 citation statements)
references
References 15 publications
1
45
0
1
Order By: Relevance
“…These data are consistent with those of others which demonstrate the existence of a p53-independent response to DNA damage (Liebermann et al, 1995) and that wild type p53 mediates the apoptotic response to anticancer drugs . Indeed, it has been previously shown in a variety of cell lines, that mutant p53 confers resistance to DNA damaging agents (Lee and Bernstein, 1993;Eliopoulos et al, 1995;Hamada et al, 1996). p53-null tumors rarely occur in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…These data are consistent with those of others which demonstrate the existence of a p53-independent response to DNA damage (Liebermann et al, 1995) and that wild type p53 mediates the apoptotic response to anticancer drugs . Indeed, it has been previously shown in a variety of cell lines, that mutant p53 confers resistance to DNA damaging agents (Lee and Bernstein, 1993;Eliopoulos et al, 1995;Hamada et al, 1996). p53-null tumors rarely occur in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of p53 mutations was found to predict worse prognosis and reduced response to therapy in many (Lowe, 1995;El Rouby et al, 1993;Wattel et al, 1994;Rusch et al, 1995;Righetti et al, 1996;Traubert et al, 1996;Hamada et al, 1996;Goh et al, 1995), though not all (Makris et al, 1995;Mathieu et al, 1995;Cote et al, 1997), tumors. Loss of wt p53 activity could potentially account fully for the increased radio-and chemoresistance of tumors bearing p53 mutations.…”
Section: Introductionmentioning
confidence: 99%
“…The absence of wild-type p53 function results in the cellular resistance to anticancer agents such as 5-FU and cisplatin in several cell lines, including gastric cancer (Nabeya et al, 1995;Harris, 1996). In addition, several investigators have demonstrated the correlation between the immunohistochemical overexpression of p53 in primary gastric cancer and the resistance to cisplatin-contained regimens (Hamada et al, 1996;Cascinu et al, 1998;Nakata et al, 1998).…”
mentioning
confidence: 99%